A study on the impact of logging and agricultural activities on the water quality planning of Tasik Chini, Pahang, Malaysia - Mohd Adam, Musa (2014)
A study on the impact of logging and agricultural activity towards water quality in Tasik Chini was carried out in July and August 2013. Seven sampling stations were selected for this study: Gumum, Jerangking, Jemberau, Batu Busuk, Melai, Mempitih, and Dam Area. Thirteen water quality parameters were considered in this study during dry and wet season periods. The parameters were then analyzed and measured according to Department of Environment Water Quality Index (DOE-WQI) and National Water Quality Standard (NWQS) for Malaysia. The water quality of Tasik Chini falls into class II according to classification using DOE-WQI. Therefore, it is suitable for recreational uses but need conventional treatment for water supply. Agricultural activity, such as palm oil plantation at Gumum, rubber plantation near Jerangking and logging activities at Bukit Tebakang near the lake did affected water quality in Tasik Chini. If these situations continued, may have caused Tasik Chini environmental degradation and may affect the aquatic life and hydrological characteristics of water system in long term deterioration.